Adobe Photoshop elements 3.0 : - Andrews, Philip (Focal Press, 2005)
The book provides an introduction to Adobe Photoshop Elements (easy to use cut down version of Photoshop)which has been updated throughout to show all the new features of version 3.0 including Photo Browser, Quick Fix Editor, Photo Creations Projects, the integrated RAW file editor and 16 bit editing support